Novel MCR Synthesis of Post Transition Metal Complexes with Substituted Hydroxy Quinolines as Potent Antimicrobial Agent - Pervaiz, Ansar; Makshoof Athar, Muhammad; Ain Khan, Misbahul; Uz Zaman, Ashhar; Pervaiz, Muhammad (Asian Journal of Chemistry, 2014)
A series of Ni(II), Cu(II) and Zn(II) complexes have been synthesized by condensation and cyclization methodology. The ligand was synthesized by MCR (multi component reaction) of ortho toluidine, ethyl acetoacetate and triethyl ortho-formate and the condensed product was further cyclized in dowtherm A. The synthesized ligand was reacted with M(CH3COO)2 (M = Ni, Cu or Zn), to get complexes. The synthesized metal complexes and ligand were characterized by FT-IR, Mass, X-ray crystallography and atomic absorption. The ligand as well as metal complexes were also screened for antimicrobial activities. The data showed that complexes exhibited more biological activities than ligand.